The relationship between gender role attitudes, attitudes toward childbearing, family functioning and attitudes toward marriage among young adults in Malaysia. - Choo, May Yan; Ng, Chloe Chu Yin; Cheong, Claryce Yong Qing (2023)
Malaysia is facing a change in the trend of marriage and family formation patterns with a significant decrease in marriage, birth, and fertility rate over the years. Consequently, these issues may lead to some negative effects. Thus, this study aims to study the relationship between gender role attitudes, attitudes toward childbearing, family functioning and attitudes toward marriage among Malaysian young adults. A quantitative cross-sectional study design with a purposive sampling method was conducted using an online survey. 100 participants were used for the final analysis with 72 females and 28 males. The participants' age ranged from 18 to 25 years. Pearson Product-Moment Correlation and simple linear regression were used to investigate the relationship between gender role attitudes, childbearing attitudes, family functioning and attitudes toward marriage. The result showed that only childbearing attitudes has a significant relationship and predictive effect with attitudes toward marriage. In conclusion, this finding provides insights to designing interventions and awareness programs that aims to increase positive attitudes towards marriage.